口蓋粘膜原発の節外性NK/T細胞リンパ腫, 鼻型の1例 - 大西, 淑美; 伊藤, 章; 石本, 俊介; 美馬, 淳子; 北村, 龍二; 松岡, 裕大 (日本口腔外科学会雑誌, 2013)
Extranodal NK/T cell lymphoma, nasal type is a rare malignant lymphoma, especially in the oral cavity. It is characterized by a necrotizing ulcer, often strongly associated with Epstein-Barr virus. We describe a case of extranodal NK/T cell lymphoma, nasal type found because of antiphlogistic-resistant swelling in the palate. A 73-year-old man was referred to our hospital because of pain and swelling in the left side of the hard palate. Computed tomography showed no evidence of bone destruction, and the symptoms did not change after antibiotic therapy. Therefore, a biopsy was performed, and immunohistochemical analyses revealed positivity for CD56, TIA-1, EBER on in situ hybridization, CD45RO (UCHL1), and CD3 and negativity for CD79a and CD20 (L26). Four courses of DeVIC (CBDCA, VP-16, IFO, DEX) were administered to the patient. There has been no sign of recurrence after chemotherapy. This case demonstrates that antiphlogistic-resistant swelling with no inflammation in the oral cavity can be a clinical sign of extranodal NK/T cell lymphoma, nasal type.